Hydrofluoric Acid Burn Management – Case Presentation - Sabina GRAMA; Andreea BULARDA; Mihaela ANDREI; Tiberiu Paul NEAGU; Serban Arghir POPESCU; Camelia Cristina DIACONU; Ovidiu Gabriel BRATU; Dan IONESCU; Liviu TIGANIUC; Ioan LASCAR (Modern Medicine)
Background: Hydrofluoric acid (HF) is an extremely dangerous weak inorganic acid, which can produce extensive burn lesions, depending especially on the solution concentration and exposure time, systemic toxicity occurring in patients with large burn areas, high concentration of acid or an extensive time of exposure. The subcutaneous inﬁltration and intravenous administration of calcium gluconate is essential for preventing dyselectrolytemia and severe pain appearance. Case summary: A 26-year-old man patient presented to our hospital after a hydrofluoric burn, secondary to an occupational accident. At the scene, the wound was irrigated with fresh water and topical calcium gluconate was applied. In the Emergency Department, we started the intravenous calcium gluconate administration, and in the Burn Unit it was injected subcutaneously and the pain was thus diminished. A prolonged QT interval was identiﬁed upon admission that has been corrected over the next few days. Particularly, the serum pseudocholinesterase levels were within normal range. The local treatment involved repeated copious lavage with sterile water and Betadine solution, the evolution being rapidly favorable with the burn lesions completely healed in the next week. Conclusion: HF burns are a very special type of chemical burn taking into account that exposure to a small quantity of solution can be life threatening and that the immediate treatment is mandatory in order to maximize the outcome. It is of vital importance that any medical facility had a chemical burn protocol.